Fitting small-group learning in first-year engineering mathematics courses - Lohgheswary, N.; A, Preethy.; R, Leelavathi. (Edelweiss Applied Science and Technology, 2026)
Even though the students were initially excited to study engineering, the course seemed to have sapped their enthusiasm. One of the factors contributing to the high first-year failure rate in the course is the difficulty of engineering mathematics. High school arithmetic is more straightforward than math in higher education. When students take drastically different courses at school and university, some first-year students find it difficult to transition. Class size is another element that affects the first-year student failure rate. Social isolation and peer competition are reduced when learning in small groups. It also promotes successful academic pursuits and positive interpersonal relationships. Students who work together to achieve learning objectives gain socially and intellectually. One challenge with small group learning is that, to avoid misunderstandings inside the group, the instructions for the group task must be clearly stated. There may be disagreements among students. Another challenge for small group learning arises when each member of the group is given the same mark for their work. Instead of one lecturer teaching over 100 students, there should be about five tutors to facilitate small group learning with the speaker. The 3P model encourages a more thorough examination of the factors affecting students’ learning results. The model’s prediction considers the student, the course, and the department’s learning environment.